PELATIHAN UJI TOURNIQUET DAN PENINGKATAN PENGETAHUAN KADER KESEHATAN DALAM MENDETEKSI SINDROM SYOK DEMAM BERDARAH - Djamaluddin, Nurdiana; Sulistiani, Ita; M.Arsad, Siti Fatimah; Djafar, Ervan (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2024)
Dengue fever is one of the most common tropical diseases that attack humans. Delay in establishing a diagnosis of dengue fever greatly determines the prognosis of the patient. The tourniquet test is one way to establish a diagnosis of dengue fever, in addition to laboratory blood tests. A positive tourniquet test indicates a manifestation of bleeding. Efforts to increase knowledge about dengue fever are very necessary. Through mentoring health cadres about dengue fever, so that it can be used as an initial step in early detection of dengue fever. Through mentoring health cadres about dengue fever, so that it can be used as an initial step in early detection of dengue fever. In addition, early treatment of dengue fever can reduce the risk of emergency conditions or death. After community service was carried out, there was an increase in public knowledge after being given information about dengue fever shock syndrome and the tourniquet test method. After the counseling, most participants understood how to eradicate mosquito nests, see signs of shock in dengue patients and how to detect patients by conducting a tourniquet test.